Biophysical Modeling to Determine the Optimization of Left Ventricular Pacing Site and AV/VV Delays in the Acute and Chronic Phase of Cardiac Resynchronization Therapy. (14th January 2017) - LEE, ANGELA W. C.; CROZIER, ANDREW; HYDE, EOIN R.; LAMATA, PABLO; TRUONG, MICHAEL; SOHAL, MANAV; JACKSON, THOMAS; BEHAR, JONATHAN M.; CLARIDGE, SIMON; SHETTY, ANOOP; SAMMUT, EVA; PLANK, GERNOT; et al.
Device Optimization for Acute and Chronic CRT: Background: Cardiac anatomy and function adapt in response to chronic cardiac resynchronization therapy (CRT). The effects of these changes on the optimal left ventricle (LV) lead location and timing delay settings have yet to be fully explored. Objective: To predict the effects of chronic CRT on the optimal LV lead location and device timing settings over time. Methods: Biophysical computational cardiac models were generated for 3 patients, immediately post‐implant (ACUTE) and after at least 6 months of CRT (CHRONIC). Optimal LV pacing area and device settings were predicted by pacing the ACUTE and CHRONIC models across the LV epicardium (49 sites each) with a range of 9 pacing settings and simulating the acute hemodynamic response (AHR) of the heart. Results: There were statistically significant differences between the distribution of the AHR in the ACUTE and CHRONIC models (P < 0.0005 in all cases). The site delivering the maximal AHR shifted location between the ACUTE and CHRONIC models but provided a negligible improvement (<2%). The majority of the acute optimal LV pacing regions (76–100%) and device settings (76–91%) remained optimal chronically. Conclusion: Optimization of the LV pacing location and device settings were important at the time of implant, with a reduced benefit over time, where the majority of the acute optimal LV pacing region and device settings remained optimal with chronic CRT.